2016
DOI: 10.1682/jrrd.2014.05.0126
|View full text |Cite
|
Sign up to set email alerts
|

Pain and psychiatric comorbidities among two groups of Iraq and Afghanistan era Veterans

Abstract: Abstract-This study aimed to (1) identify the prevalence and severity of pain and psychiatric comorbidities among personnel who had been deployed during Operation Iraqi Freedom (OIF), Operation Enduring Freedom (OEF), and Operation New Dawn (OND) and (2) assess whether the Department of Veterans Affairs (VA) Polytrauma System of Care and an OIF/OEF/OND registry reflect real differences among patients. Participants (N = 359) were recruited from two VA hospitals. They completed a clinical interview, structured d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…Full details of the parent study protocols, informed consent procedures, and Institutional Review Board approvals are published elsewhere. 8 Informed consent procedures were approved by the Institutional Review Boards and Research and Development Committees for each of the two VA facilities (one northern and one southeastern) that conducted participant enrollment and data collection. As secondary data analysis of existing, de-identified clinical information, the current study was exempt from human subject review by the Institutional Review Board of Oregon Health & Science University.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full details of the parent study protocols, informed consent procedures, and Institutional Review Board approvals are published elsewhere. 8 Informed consent procedures were approved by the Institutional Review Boards and Research and Development Committees for each of the two VA facilities (one northern and one southeastern) that conducted participant enrollment and data collection. As secondary data analysis of existing, de-identified clinical information, the current study was exempt from human subject review by the Institutional Review Board of Oregon Health & Science University.…”
Section: Methodsmentioning
confidence: 99%
“… 5 Veterans are also at higher risk for other debilitating mental health conditions, including post-traumatic stress disorder (PTSD) and traumatic brain injury. 6 8 Adequately assessing health needs of returning service members is important both for providing clinical care and allocating resources.…”
Section: Introductionmentioning
confidence: 99%
“…Studies 4 , 5 , 6 , 7 , 8 of veterans who served in Operation Enduring Freedom, Operation Iraqi Freedom, or Operation New Dawn have shown that from 40% to more than 80% report experiencing chronic pain after deployment. More than half of these soldiers describe pain that is moderate to severe 6 , 8 occurring predominantly in the back, legs, shoulders, neck, and head. 5 , 7 Such pain is frequently reported as lasting longer than 1 year, with more than half experiencing pain almost every day, if not constantly.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Chronic pain in veterans is associated with other significant problems, such as functional disability, vocational limitations, family discord, greater health care use, traumatic brain injury, and psychiatric comorbidities, including posttraumatic stress disorder (PTSD), major depressive disorder, and substance abuse that includes opioid misuse. 5 , 8 , 9 , 10 , 11 , 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…Chronic (noncancer) pain generally refers to intractable pain that exists for three or more months and does not resolve in response to treatment. Given the high prevalence of chronic pain among veterans (Haskell, Heapy, Reid, Papas, & Kerns, ; Lew et al., ; Phillips et al., ), related treatments and interventions have become a priority for the Department of Veterans Affairs (). The objective has been to provide comprehensive and integrated treatment to improve the quality of life for veterans with chronic pain.…”
Section: Introductionmentioning
confidence: 99%